Smart Attendance System using Face Recognition - Viswanathan, Jayaraj; E, Kuralamudhan; S, Navaneethan; S, Veluchamy (EAI Endorsed Transactions on Scalable Information Systems, 2024)
Face recognition offers a wide range of valuable applications in social media, security, and surveillance contexts. The software used for building facial recognition algorithms is Python and OpenCV. "Attendance using Face Recognition" is a method for tracking and managing attendance that makes use of facial recognition technology. By seamlessly integrating the 'Face Recognition' module, a native Python feature, and the OpenCV library, our system excels in accuracy and dependability. The system then stores attendance records in a database and provides real-time reports. In this article, we demonstrate how to create a face recognition system in Python utilizing the built-in "Face Recognition" module and the OpenCV library. Our results show that our system achieves high accuracy and robustness while being efficient and scalable, catering to a wide spectrum of educational institutions, organizations, and enterprises.
Keywords: Computer Vision; Machine Learning; Face Recognition; Open CV; Facial feature extraction